Program Bimbingan Belajar Gratis Bahasa Indonesia, Matematika, IPS, dan Bahasa Inggris di SD Negeri 035950 Silencer - Usman Sidabutar; Hana Grace Hutagalung; Desi Sastria Lumban gaol; Dian Nopitasari Purba; Sandly D Sihotang; Irene Anjeli Purba (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Tutorial Learning in education is a part of creativity to increase an innovative and adaptive in learning systems by which the curriculum applied through the teaching learning process. In concerned to global demand as the digital base of manner in academics, the students and lecturers of the Faculty of Teacher Training, University of HKBP Nommen Medan carried out Pengabdian Kepada Masyarakat (PKM) entitled "Program of Learning Tutorial of Bahasa Indonesia, Mathematics, Social Sciences, and English in SD Negeri 035950 Silencer, Dairi Regency. This tutorial learning was aimed at the encouragement and the improvement of the quality of the teaching and learning process which is ultimately expected to the increase of the academic achievement on students’ perceptions in accordance to their respective efforts and abilities. Having done the tutorial learning, students are more enthusiastic about doing school assignments well and no tasks are neglected because of the guidance. In addition, participants' understanding of the subject matter at school was further increased by the material being taught during class meetings